Comparative Analysis of Attack Graphs - Aslanyan, Levon H.; Alipour, Daryoush; Heidari, Minoosh (Mathematical Problems of Computer Science, 2021)
It is well-known that nowadays computers and networks that are unique in their computational and service provision power have also major weaknesses and vulnerabilities that can be exploited by outsiders in compromising the valuable data and knowledge. Network administrators and network security analysts must be aware of different properties of current software solutions and diversity of problems regarding the possible protection of network assets. This means that they must know and use the latest and newest types of vulnerabilities, techniques and tools. “Attack Graphs” present formalized network maps and help with analysis of possible vulnerabilities that may exist in the network. Hence, in this paper we will describe some basic concepts that can be used to understand and generate the attack graphs.